The Effect of Information on Voter Turnout: Evidence from a Natural Experiment - David Dreyer Lassen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2004)
Do better informed people vote more? Recent theories of voter turnout emphasize a positive effect of being informed on the propensity to vote, but the possibility of endogenous information acquisition makes estimation of causal effects difficult. I estimate the causal effects of being informed on voter turnout using unique data from a natural experiment Copenhagen referendum on decentralization. Four of fifteen districts carried out a pilot project, exogenously making pilot city district voters more informed about the effects of decentralization. Empirical estimates based on survey data confirm a sizeable and statistically significant causal effect of being informed on the propensity to vote.
Keywords: 330; voter turnout; information and voting; political participation; natural experiment; Informationseffizienz; Test; Kopenhagen; Wahlbeteiligung